“GENOCIDE”, “HATE-SPEECH”, AND “PEACE AS WAR”: From the Dayton peace implementation to a July 11, 2018 Srebrenica-related tweet - Pehar, Dražen (Politeia, 2020)
This essay deals with all key responses to the tweet about the Srebrenica “genocide” Rajko Vasić published on 11 July 2018, interpreting those as a mini-model to elucidate the entire period of the Dayton peace implementation. The essay demonstrates that the international community, including primarily the US and the UK, relates to the peace implementation as a process of continuing war in Bosnia-Herzegovina by other means. “Hate speech” perspective and ICTY Genocide indictments/verdicts are explained here as an auxiliary tool to achieve the very same purpose. Most importantly, it is argued here, and supported through a number of examples, that the issue of meaning as attributed to one’s political interlocutor, or a treaty or legislation, is preponderant in politics. Lastly, the author presents details from the UN Security Council July 8, 2015 session to illustrate the key conclusions of his analysis.